3D “House of Cards” Structured Composites of Zn/Ga Layered Double Hydroxide/Molybdenum Disulfide with Potential Application for Impedance Respiratory Frequency Sensor - Xu, Qingyue; Li, Wenjing; Qi, Qi; Guo, Ying (ACS applied electronic materials, 2023)
Respiration is an important physiological signal that can be used to monitor human health and activity. This study presents a high-performance inorganic composite-based humidity sensor for respiration monitoring. The sensor is composed of a 3D nanostructure of ZnGa-layered double hydroxide (ZnGa-LDH) growing in situ on negatively charged MoS2 wafers, obtained by co-precipitation. By adjusting the MoS2 content, the resulting ZnGa-LDH/MoS2 composite displays a 3D “house of cards” structure with a larger surface area than pure ZnGa LDH or MoS2. The sensor exhibits nearly 3 orders of magnitude impedance change from the humidity range of 11% to 95% RH, fast response/recovery time of 1.5/5 s, hysteresis difference of 2.93%, and long-term stability and high repeatability. The optimized humidity sensor can distinguish between different breathing patterns, as well as the breathing rate/depth of the subject. The conductive mechanism of the material has also been analyzed by combining with the complex impedance curve of the material. This study not only provides an easy approach to adjust the hydrophilic/hydrophobic surface of the materials to control the humidity sensing ability but also develops a humidity sensor that can reflect the breathing conditions of the human body, potentially having applications in respiratory monitoring.